2015
DOI: 10.1016/j.mbs.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A model for the coupled disease dynamics of HIV and HSV-2 with mixing among and between genders

Abstract: Evidence indicates that those with genital herpes (HSV-2) infections have greater risks of infection by HIV; and, once co-infected, are more likely to transmit HIV. To better understand the interactions between HIV and HSV-2, we construct a mathematical model that describes the joint dynamics. A new feature of this model is the inclusion of both heterosexual and homosexual interactions. We derive and interpret the basic and invasion reproduction numbers for HIV and HSV-2 using the approach of next-generation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In order to find an optimal solution of model system (17), first let us define the Hamiltonian functions H for the optimal control system (17) as…”
Section: Optimal Control Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find an optimal solution of model system (17), first let us define the Hamiltonian functions H for the optimal control system (17) as…”
Section: Optimal Control Problemmentioning
confidence: 99%
“…With HSV-2 being a pathway for the transmission of HIV, this has motivated many authors to look at HIV/HSV-2 co-infections. A number of mathematical models have looked into mathematical modelling of HIV and HSV-2 co-infections from a number of different issues [1,[17][18][19][20]25]. In contrast to other STIs such as chlamydia, gonorrhea, syphilis and trichomoniasis, infection with HSV-2 or HIV is lifelong, and, once established, there is currently no treatment to eliminate.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing body of literature, such as ( Alvey et al., 2015 , Gao et al., 2016 , Mutua et al., 2015 ) among others, investigating the co-infection dynamics of various diseases, which greatly improve our understanding of pathogen evolution. Unluckily, very few theoretical studies, except ( Slater et al., 2013 , Tang et al., 2016 ) have been performed to address the co-infection of pathogens for vector-borne diseases, especially for tick-borne pathogens.…”
Section: Co-infection Of Ixodes Tick-borne Pathogementioning
confidence: 99%
“…Foss et al [17], developed a dynamical model to estimate the HIV infection due to HSV-2 in heterosexual population. Alvey et al [18], developed a model that takes into account the transmission through either homosexual or heterosexual behaviour and investigate the impact of the coupled dynamics of HIV and HSV-2. Their results showed that homosexual transmission has great impact on the disease prevalence.…”
Section: Introductionmentioning
confidence: 99%